Bacterial and viral infections among adults hospitalized with COVID‐19, COVID‐NET, 14 states, March 2020–April 2022. Issue 3 (2nd March 2023) - Shah, Melisa M.; Patel, Kadam; Milucky, Jennifer; Taylor, Christopher A.; Reingold, Arthur; Armistead, Isaac; Meek, James; Anderson, Evan J.; Weigel, Andy; Reeg, Libby; Como‐Sabetti, Kathryn; Ropp, Susan L.; et al.
Abstract: Background: Bacterial and viral infections can occur with SARS‐CoV‐2 infection, but prevalence, risk factors, and associated clinical outcomes are not fully understood. Methods: We used the Coronavirus Disease 2019‐Associated Hospitalization Surveillance Network (COVID‐NET), a population‐based surveillance system, to investigate the occurrence of bacterial and viral infections among hospitalized adults with laboratory‐confirmed SARS‐CoV‐2 infection between March 2020 and April 2022. Clinician‐driven testing for bacterial pathogens from sputum, deep respiratory, and sterile sites were included. The demographic and clinical features of those with and without bacterial infections were compared. We also describe the prevalence of viral pathogens including respiratory syncytial virus, rhinovirus/enterovirus, influenza, adenovirus, human metapneumovirus, parainfluenza viruses, and non‐SARS‐CoV‐2 endemic coronaviruses. Results: Among 36 490 hospitalized adults with COVID‐19, 53.3% had bacterial cultures taken within 7 days of admission and 6.0% of these had a clinically relevant bacterial pathogen. After adjustment for demographic factors and co‐morbidities, bacterial infections in patients with COVID‐19 within 7 days of admission were associated with an adjusted relative risk of death 2.3 times that of patients with negative bacterial testing. Staphylococcus aureus and Gram‐negative rods were the most frequently isolated bacterial pathogens. Among hospitalized adults with COVID‐19, 2766 (7.6%) were tested for seven virus groups. A non‐SARS‐CoV‐2 virus was identified in 0.9% of tested patients. Conclusions: Among patients with clinician‐driven testing, 6.0% of adults hospitalized with COVID‐19 were identified to have bacterial coinfections and 0.9% were identified to have viral coinfections; identification of a bacterial coinfection within 7 days of admission was associated with increased mortality.